2015
DOI: 10.1039/c4ta05877a
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced photovoltaic performance of meso-porous SnO2 based solar cells utilizing 2D MgO nanosheets sensitized by a metal-free carbazole derivative

Abstract: Herein, we report a power conversion efficiency of 3.71% using mesoporous SnO2 in combination with 2D MgO nanosheets, sensitized by a metal free carbazole dye.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
22
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 37 publications
(24 citation statements)
references
References 39 publications
1
22
1
Order By: Relevance
“…The wide range of work functions in TMO enables them for using as an antireflection coating (ARC) on photovoltaic devices to improve photon to electron conversion (PEC) efficiency [4]. The ARCs are characterized by broad bandgap along with wide optical transmission ranging from700 to 1000 nm, and surface roughness [5]. Hence, ARC's developed in nanometer thickness can enhance the PEC efficiency of solar cells by increasing light trapping in the active region [6].…”
Section: Introductionmentioning
confidence: 99%
“…The wide range of work functions in TMO enables them for using as an antireflection coating (ARC) on photovoltaic devices to improve photon to electron conversion (PEC) efficiency [4]. The ARCs are characterized by broad bandgap along with wide optical transmission ranging from700 to 1000 nm, and surface roughness [5]. Hence, ARC's developed in nanometer thickness can enhance the PEC efficiency of solar cells by increasing light trapping in the active region [6].…”
Section: Introductionmentioning
confidence: 99%
“…From the Bode phase plot, the values of τ e (photoinduced electron lifetime) are evaluated using the following relation, τ e = 1/(2π f p ), where f p is the observed maximum peak frequency in the mid-frequency region. 25 It has been found that the τ e values for different photoanodes are 3.9, 5.1, 10.9, and 12.6 ms for SnO 2 nanoparticle, SZ 10 , SZ 20 , and SZ 30 devices. The gradual increase in the photoinduced electron lifetime for the composite-based devices as compared to that for pristine SnO 2 photoanode-based device with an increase in the meso-ZnO HS content also validates the interference created by addition of meso-ZnO HS, acting as a partial barrier for photoinduced electrons to undergo recombination at the semiconductor/dye/electrolyte interface.…”
Section: Results and Discussionmentioning
confidence: 95%
“…20 “Bare SnO 2 -nanoparticle (NP)-based devices made from SnO 2 nanoparticles only (size ∼20 nm) with the mostly used Ru-based N719 dye rarely show power conversion efficiencies more than PCE ∼2%”. 2123 A very convenient strategy to overcome the adverse issues in the case of SnO 2 -based photoanode is to make composite photoanodic architectures with other wide-band-gap metal oxides such as TiO 2 , 24 MgO, 25 and ZnO. 2629 It has been seen that in the case of SnO 2 -based devices the composite photoanode architecture has shown substantial improvement in device performances, resulting from a reduced reverse tunneling probability of photogenerated electrons.…”
Section: Introductionmentioning
confidence: 99%
“…[ 41 ] SnO 2 was first applied as an ETL in dye‐sensitized solar cells and then became popular for utilization in PSCs. [ 42 ] The high transmittance of SnO 2 enables PSCs to achieve higher performance within the visible region of the solar radiation spectrum. [ 43 ] In addition, the wide bandgap and well‐matched energy band alignment contribute to a strong hole‐blocking effect and rapid charge extraction at the interface.…”
Section: Introductionmentioning
confidence: 99%